Understanding and Promoting Menstrual Hygiene Knowledge among Adolescent Girls : A Study at a Public High School in Yogyakarta, Indonesia - Amalia, Amalia Ade Finantika; Diniyah, Kharisah (The Indonesian Institute of Science and Technology Research, 2023)
Based on data from the World Health Organization (WHO), the global prevalence of reproductive tract infections among teenagers ranged from 35% to 42% in 2012. In the specific context of Indonesia, statistics reveal that out of the country's 69.4 million adolescents, a staggering 63 million exhibited concerning hygiene behaviours. Additionally, it was noted that up to 5.2 million young women frequently experienced discomfort during menstruation due to inadequate hygiene practices. This research aims to provide insights into the knowledge and practices of menstrual hygiene among adolescents at a public high school in Yogyakarta, Indonesia. The study employed a quantitative descriptive approach and was conducted as a cross-sectional investigation. The results revealed that most respondents exhibited a high level of readiness and knowledge, with 91.6% categorised as having good knowledge, while 8.3% demonstrated sufficient ability. Notably, none of the participants fell into the category of inadequate knowledge. Regarding preparation for menstruation, 44 respondents were well-prepared, whereas four respondents exhibited sufficient preparation. These findings shed light on the importance of promoting menstrual hygiene education and practices among adolescents in Indonesia to improve overall reproductive health and well-being.